Myocardial Injury Biomarkers in Newborns with Congenital Heart Disease - Ana Luisa Neves; Maria Cabral; Adelino Leite-Moreira; José Monterroso; Carla Ramalho; Hercília Guimarães; Henrique Barros; João T. Guimarães; Tiago Henriques-Coelho; José C. Areias (Pediatrics and Neonatology)
Troponin I, myoglobin, and creatine kinase-MB mass (CK-MB) are biomarkers of cardiomyocyte injury widely used in the management of adult patients. The role of these biomarkers in newborns is still not established. The purpose of this study was to evaluate the value of cardiac injury biomarkers in newborns with congenital heart disease. Methods: From August 2012 to January 2014, 34 newborns with a prenatal diagnosis of congenital heart disease were admitted consecutively to a neonatal intensive care unit. As controls, 20 healthy newborns were recruited. Plasma levels of cardiac biomarkers (troponin I, myoglobin, and CK-MB) were evaluated, and echocardiography was performed to evaluate cardiac function on D 1. Patients were followed during the first 28 days of life and, according to outcome, categorized as surgical or conservative treatment group. Results: Median (P25–75) levels of CK-MB were higher in patients who underwent cardiac surgery in the neonatal period [7.35 (4.90–13.40) ng/mL] than in patients who were discharged home without surgery [4.2 (2.60–5.90) ng/mL; p = 0.032]. A CK-MB cutoff of ≥ 4.6 ng/mL showed sensitivity of 87.5% and specificity of 63.6%. Troponin I and myoglobin levels were not significantly different between conservative and surgical treatment groups. CK-MB levels correlated with the tissue Doppler image of the mitral valve lateral annulus peak early/late diastolic velocity ratio (ρ = −0.480, p = 0.018). Conclusion: CK-MB levels during the first hours of life were higher in newborns that needed neonatal cardiac surgery, and these levels may be an indicator of myocardial diastolic function.